Metallurgical Evaluation of the Hoidas Lake Rare Earth Deposit - Corby Gerard Anderson (Metallurgical & Materials Engineering, 2020)
Hoidas Lake lies in the Northern Rae Geological Province, in the general vicinity of many of Saskatchewan's large uranium mines. The mineralogy of the Hoidas Lake rare-earth deposit differs from most other such deposits in that it is hosted in equal abundance in veins containing apatite and allanite mineral groups. Hoidas Lake also differs from other deposits in that it contains a significant amount of heavy rare-earth elements, such as dysprosium. This abundance of heavy Rare Earth Elements (REE’s) is significant, as there is a growing demand for the heavier rare earths in high-tech manufacturing (such as the use of dysprosium in the manufacturing of hybrid car components). Recently, metallurgical testing was performed on a Hoidas Lake REE deposit composite. These investigations included characterization, flotation testing, heavy media separation, magnetic separation testing, whole ore leaching studies, bond work index grindability testing, and relative abrasion index testing. This paper summarizes this research effort.